7C.05: PREDICTORS OF INCREASED ARTERIALL STIFFNESS IN HYPERTENSIVE PATIENTS - Tautu, O; Darabont, R; Onciul, S; Deaconu, A; Petre, I; Andrei, R D; Dragoescu, B; Dorobantu, M (Journal of hypertension, 2015)
To evaluate arterial stiffness in hypertensive patients and to identify predictors of increased arterial stiffness. 798 hypertensives identifyed in SEPHAR II survey (mean age 51.46 ± 5.82 years; 48.1% females) were evaluated by a study questionnaire, blood pressure and antropometric measurements and laboratory work-up. Studied parameters definitions were: increased arterial stiffness: PWVao > 10m/s, visceral obesity: waist circumference >102 cm in men and > 88 cm in women, diabetes mellitus assessed by current ADA criteria, lipid dissorders by NCEP ATPIII recomendations and increased BP variability: mean SBP' standard deviation (s.d.) values above the 75th percentile. Subclinical organ damage definitions were: left ventricular hypertrophy (LVH) on ECG assessed by Cornell product,urinary albumin to creatinine ratio (UACR) of 30 - 300 mg/g) and eGFRCKD-EPI < 60-90 ml/min/1.73m2. Cardiovascular risk was assessed by SCORE system. Binary logistic regression using stepwise LR method (coliniarity analysis and adjustmens for major confunders) was used to validate predictors of increased arterial stiffness. Mean values of studied parameters were: BP-149.96 ± 20.94/89.18 ± 11.54, SBP's.d -7.73 ± 8.6mmHg (24.9% of subjects with increased SBP variability), PP-60.99 ± 17.95mmHg, HR-73.75 ± 10.89bpm. Mean PWVao-10.19 ± 2.22m/s, 27.2% of the study sample having PWVao >10m/s. Regression analysis validated as predictors of increased PWVao: age group [OR: 5.53; 95%CI (2.62-13.21)], hypertrygliceridemia [OR: 1.82; 95%CI (1.18-2.81)], low-HDL cholesterol [OR: 1.62; 95%CI (1.05-2.49)], SBP's.d values above 8,49mmHg [OR: 2.14; 95%CI (1.16-3.95)], UACR 30-300 mg/g [OR: 3.46; 95%CI (1.43-8.36)], LVH on ECG [OR: 2.14; 95%CI (1.79-7.34)], eGRFCKD-EPI < 60-90 ml/min/1.73m2 [OR: 1.49; 95%CI (1 -2.23)], lack of BP treatment control [OR: 5.53; 95%CI (2.62-13.21)] and high/very high CV risk category by SCORE [OR: 1.69; 95%CI (1.02-2.83)]. Age above 40 years, atherogenic dislipidemia, increased SBP variability, the lack of optimal BP treatment control and the presence of subclinical organ damage, may be considered as predictors of an increased arterial stiffness in hypertensive patients, placing these patients at an increased risk of major CV events.